Factors Associated with the Risk of Autism in Children Under Five Years of Age: A Path Analysis Evidence from Banten - Astuti, Fitriyani Dwi; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2018)
Background: Autism, now increasingly referred to as autism spectrum disorder (ASD) is a set of clinical phenotypes mirroring an early-onset neurodevelopmental disorder affecting social communication, imagination, and behavior. Children with ASD develop differently from other children. They also have challenges in interacting and communicating with others. These challenges can affect their development and learning. This study aimed to determine factors associated with the risk of autism in children under five. Subjects and Method: This was a case control study carried out at two special schools for children with development problem in Tangerang, Banten, from February to March 2018. A sample of 200 children aged 1-5 years was selected by fixed disease sampling, consisting of 50 children with autism and 150 normal children. The dependent variable was autism. The independent variables were family income, maternal education, maternal age, gestational stress, chemical exposure, nutritional intake, fever at pregnancy, growth and development impairment, and mumps-measles-rubella (MMR) vaccine. Data on immunization status, growth and development were taken from medical record. Data on the other variables were collected by questionnaire.The data were analyzed by path analysis. Results: The risk of autism increased with chemical exposure (b= 2.86; 95%CI= 0.77 to 4.96; p= 0.007), gestational stress (b= 2.45; 95% CI= 0.60 to 4.30; p= 0.010), growth and development impairment (b= 1.69; 95% CI= -0.24 to 3.61; p= 0.086), and maternal age ?35 years (b= 2.82; 95% CI= 0.73 to 4.92; p= 0.008). Autism decreased with good nutritional intake (b= -2.08; 95%CI= -3.88 to -0.28; p= 0.023). The risk of autism was indirectly affected by fever at pregnancy, chemical exposure, family income, and maternal education. MMR vaccine did not affect the incidence of autism (b= 1.12; 95% CI= -2.11 to 4.36; p= 0.500). Conclusion: The risk of autism increases with chemical exposure, gestational stress, growth and development impairment, maternal age ?35 years, and decreases with good nutritional intake. MMR vaccine does not affect the incidence of autism in children. Keywords: autism, chemical exposure, growth and development impairment, MMR vaccine, children under five Correspondence: